P.077 Mixed autoimmune hemolytic anemia: an unusual cause of ischemic stroke and extensive cerebral microbleeds. (November 2021) - Wan, M; Ganesh, A; Grassi, C; Demchuk, A
Abstract : Background: Mixed autoimmune hemolytic anemia (mAIHA) is a rare autoimmune disorder that results in hemolysis with thrombotic complications like ischemic stroke. This is the first case report of cerebral microbleeds secondary to mAIHA. Methods: A literature review of mAIHA and cerebral microbleeds was conducted using the PubMed and Ovid MEDLINE databases from 1980 to 2021. Results: A 76 year old male with congenital deafness and rheumatoid arthritis presented with diffuse livedo reticularis and abdominal pain. He had fulminant hemolysis with new neurologic deficits and altered mental status. CT/CTA of the head and neck were unremarkable. MR brain revealed extensive cerebral microbleeds and multi-territory ischemic strokes. He was diagnosed with mAIHA, started on pulse methylprednisolone, and had no further microbleeds on follow-up MRI. From his clinical picture, common causes of cerebral microbleeds were ruled out such as cerebral amyloid angiopathy and hypertension. The pathogenesis of his microbleeds may be from concomitant severe hypoxia or a prothrombotic state, both previously reported in the literature. Conclusions: This is the first case report of extensive cerebral microbleeds secondary to mAIHA. When a patient develops acute neurologic deficits in the context of mAIHA, extensive cerebral microbleeds may be present possibly due to concomitant severe hypoxia versus a prothrombotic state.